1979
DOI: 10.1111/j.2042-3306.1979.tb01355.x
|View full text |Cite
|
Sign up to set email alerts
|

A Re‐evaluation of the D (+) Xylose Absorption Test in the Horse

Abstract: SUMMARY The absorption of d‐xylose forms the basis of a useful screening test in the investigation of small intestinal disorders in the horse. A comparison has been made of different assay methods and there was no significant difference between the results obtained with the parabromoaniline (PBA) method or the ferric chloride‐orcinol (FCO) method. The orthotoluidine method was unsatisfactory. The anticoagulant agent did not affect the test. A dose of 0.5 g commercial grade xylose/kg body weight as a 10 per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…Plasma xylose concentrations were determined by Autoanalyzer (Tarrytown, NY, USA) colorimetry using the ferric chloride‐orcinol technique (R oberts and N orman 1979). The dry matter, ash and ether extract in the feed and faeces were analysed by standard methods (AOAC 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma xylose concentrations were determined by Autoanalyzer (Tarrytown, NY, USA) colorimetry using the ferric chloride‐orcinol technique (R oberts and N orman 1979). The dry matter, ash and ether extract in the feed and faeces were analysed by standard methods (AOAC 1975).…”
Section: Methodsmentioning
confidence: 99%
“…Turkey plasma D-xylose concentrations following oral administration of D-xylose (.5 g/kg body weight) most closely resemble those seen in normal humans (Wolfish et al, 1955;Dawson, 1965), are lower than values commonly observed in dogs (Hill et al, 1970), but are greater than those seen in cattle (Pearson and Baldwin, 1981) and horses (Roberts, 1974;Bolton et al, 1976;Roberts and Norman, 1979). Variation between individual xylose absorption curves, regardless of species, suggests that results obtained from testing a single animal could be difficult to interpret.…”
Section: Discussionmentioning
confidence: 64%
“…The plasma D-xylose test has been used in the study of intestinal malabsorption in dogs (Hill et al, 1970;Hill and Kelly, 1974), horses (Roberts, 1974;Bolton et al, 1976;Roberts and Norman, 1979;Dietz, 1981), cattle (Mavromichalis et al, 1977;Woode et al, 1978;Pearson and Baldwin, 1981), and cats (Merritt, 1980;Emms et al, 1983), but not in fowl. In animals, determination of percent xylose recovered in urine is severely limited by problems associated with prolonged urine collection periods (8 hr in man) and the fact that not all animals produce urine that can be readily collected or separated from feces (birds, reptiles, fish).…”
Section: Introductionmentioning
confidence: 97%
“…160,619 Although the plasma concentration of glucose may reflect glucose metabolism as well as absorption from the gastrointestinal tract, the assay is reliable in the diagnosis of significant malabsorptive conditions. Absorption tests are used primarily in horses with chronic diarrhea or weight loss to evaluate the small intestinal absorptive capacity.…”
Section: Ancillary Diagnostic Testsmentioning
confidence: 99%